Loss to follow-up and Associated Factors of Patients in the National AIDS Program in Thailand. Issue 6 (August 2018) - Teeraananchai, Sirinya; Kerr, Stephen J; Ruxrungtham, Kiat; Avihingsanon, Anchalee; Chaivooth, Suchada; Teeraratkul, Achara; Bhakeecheep, Sorakij; Ongwandee, Sumet; Thanprasertsuk, Sombat; Law, Matthew G
Background: Loss to follow-up (LTFU) is a crucial indicator to evaluate the effectiveness of HIV care and treatment programmes. We assessed the LTFU rate and associated factors of Thai HIV-infected patients who enrolled in the National AIDS Program (NAP) for two periods: prior to (pre-ART) and after starting ART (ART-patients). Methods: Thai HIV patients aged ≥15 years enrolled in NAP from 2008 to 2014. Vital status was ascertained by linkage with the National Death Registry. Competing risk models were used to calculate the adjusted sub-distribution hazards (aSHR) for LTFU for pre-ART and ART-patients, with death considered as a competing risk. Results: A total of 157, 026 patients registered in care and were included in analyses. The cumulative incidence of LTFU in pre-ART patients at 1 year was 10.2%, whereas in ART-patients it was 12.8%. Among pre-ART patients, younger age (<30 versus ≥45 years, aSHR 1.60, 95% CI 1.49, 1.72), less advanced HIV stage (aSHR 1.29, 95% CI 1.21, 1.37) and higher CD4 + T-cell count (≥350 versus <100, aSHR 6.31, 95% CI 5.74, 6.95) had a higher chance of LTFU. ART-patients with high baseline CD4 + T-cell count (CD4 ≥350 versus CD4 <50, aSHR 2.06, 95% CI 1.97, 2.15) and non-advanced HIV stage had increased risk of LTFU. Conclusions: Our findings provide new evidence of the LTFU rate in Thai HIV-infected patients in NAP. Emphasis needs to be placed on improving follow-up in all patients with higher CD4 + T-cell counts. LTFU will be important to monitor as programmes move to commence ART regardless of CD4 + T-cell count.